Pedagogical or punitive?: The academic integrity websites of Ontario universities - Griffith, Jane (Canadian Journal of Higher Education, 2013)
This study is a snapshot of how Ontario universities are currently promoting academic integrity (AI) online. Rather than concentrating on policies, this paper uses a semiotic methodology to consider how the websites of Ontario’s publicly funded universities present AI through language and image. The paper begins by surveying each website and documenting emerging language-based trends like interpellating different audiences, inducting students into a larger scholarly community, and appealing to peer disapproval. The paper also records how these websites visually communicate AI through images and video, arguing that image and text inform one another in a two-way relationship: for example, a punitive image may undermine an otherwise textually pedagogical website. Overall, the majority of Ontario websites have a decidedly educative mandate in their online AI resources, aligning with current AI scholarship that lauds education rather than after-the-fact punishment.